2007
DOI: 10.1002/ajh.20806
|View full text |Cite
|
Sign up to set email alerts
|

Osseous metaplasia in diffuse large B‐cell lymphoma of the kidney

Abstract: A 57-year-old female with a history of diffuse large B-cell lymphoma (DLBCL) presented with a renal mass. Microscopic analysis of the nephrectomy specimen revealed DLBCL, confirmed by immunohistochemical analysis (CD45, CD20, CD3, pan-keratin) and polymerase chain reaction (PCR). Multiple spicules of metaplastic bone were identified within the tumor mass, but not within the uninvolved kidney parenchyma. No evidence of bone or dystrophic calcification was detected on the pre-nephrectomy computerized tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…IL-6 is may be the responsible factor. Although this interleukin is considered as a bone resorption factor, [13, 14] it may play a role in bone formation and osteoblast proliferation, too [10, 13]. Also amyloid deposit may be seen in CD [9], and this could be site for osseous metaplasia, but no amyloid deposit was seen in our case.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…IL-6 is may be the responsible factor. Although this interleukin is considered as a bone resorption factor, [13, 14] it may play a role in bone formation and osteoblast proliferation, too [10, 13]. Also amyloid deposit may be seen in CD [9], and this could be site for osseous metaplasia, but no amyloid deposit was seen in our case.…”
Section: Discussionmentioning
confidence: 75%
“…According to clinical presentation CD may be unicentric or multicentric [16, 9, 10]. The unicentric form is usually of hyaline-vascular type, pauci symptomatic with favorable prognosis and commonly involves the mediastinum [3, 4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Osseous metaplasia may develop after trauma, or with a post-traumatic hematoma and soft-tissue tumors, especially slow growing tumors treated with radiation 3. Several cases of osseous metaplasia have been reported that were related to conditions, including tubular adenoma of the colon, diffuse large B-cell lymphoma and amyloid-producing dyscrasia 5,9. Few studies have reported benign breast lesions that were seen as osseous metaplasia 10.…”
Section: Discussionmentioning
confidence: 99%